Presenteeism and mental health of workers during the COVID-19 pandemic: a systematic review - García-Iglesias, Juan Jesús; Gómez-Salgado, Juan; Apostolo, Joao; Rodrigues, Rogério; Costa, Emília Isabel; Ruiz-Frutos, Carlos; Martínez-Isasi, Santiago; Fernández-García, Daniel; Vilches-Arenas, Ángel (Frontiers in Public Health, 2023)
Background A large number of workers attend work despite being ill. Attending work during sickness can have a number of consequences for the worker (e.g., worsening of physical and mental condition), for co-workers, and for the company, and for service users. Objectives The aim of this study was to assess the factors influencing presenteeism and mental health of workers during the COVID-19 pandemic. Methods A systematic review following the PRISMA format was conducted in the PubMed, Scopus, Web of Science (WoS), Cumulative Index to Nursing and Allied Health Literature (CINAHL), PsycInfo, and ScienceDirect electronic databases in January 2023, using the following key words: Presenteeism, Mental Health, and COVID-19. The eligibility criteria applied were original articles published in English, Spanish, French, German, and Portuguese, workers during the COVID-19 pandemic (data collection date: January 01, 2020 – January 01, 2023), and articles assessing at least one measure of presenteeism and mental health status. Methodological quality was assessed using the critical appraisal tools of the Joanna Briggs Institute. The followed protocol is listed in the International Prospective Register of Systematic Reviews (PROSPERO) with code CRD42023391409. Results A total of 25 studies were included in this review recruiting a total of 164,274 participants. A number of factors influencing mental health and sickness presenteeism were identified: (1) mental health-related factors (burnout [in 4 studies], stress [in 9 studies], depression [in 1 study], fear of COVID-19 [in 1 study], no well-being [in 2 studies], etc.); (2) individual factors (health status [in 1 study], being young [in 1 study], workers who experienced interrupted medical care [in 2 studies], having a chronic disease [in 1 study], etc.); (3) factors related to the situation caused by COVID-19 (confinement, symptoms, loss of contract, risk of bankruptcy, etc. [in 1 study each one]); and (4) factors derived from working conditions (organisational support [in 1 study], patient care [in 1 study], work functioning or task performance impairment [in 4 studies], work fatigue [in 2 studies], safety climate [in 1 study], workload [in 1 study], etc.). Conclusion Identifying the key determinants of presenteeism and understanding the phenomena and origins of sickness presenteeism will help to create a safe working environment and optimal organisational systems to protect vulnerable workers in a pandemic context. Systematic review registration The unique identifier is CRD42023391409.